Knowledge transfer programme and improvement of marine fish seed production in Setiu, Terengganu Darul Iman - Abd Rahim, Abdullah; Kamarudin, Mohd Salleh; Christianus, Annie; Mustaffa, Amirul Farhan; Mohd Daud, Hassan (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
The hatchery production of consistently high quality fish larvae is a major challenge in marine fish culture. Knowledge of broodstock and larval fish biology, live food culture techniques and biosecurity procedures can help alleviate this challenge. Such knowledge are being transferred to Ilham SH Aqua & Trading, a marine fish hatchery based in Setiu, Terengganu. The hatchery has been producing grouper and seabass fingerlings for the local market since 2003, but poor survivals lead to inconsistent production and hampered further growth. Since the programme started, several areas where improvements could be made have been identified. Preliminary assessments indicated that improvement in handling of larval fish and nutrition of live food would help to improve survivals. Specific procedures to improve larval fish handling have been recommended and are being monitored. Microalgae production using closed system and more sanitary procedures are being implemented to reduce bacterial contamination during culture.